Anti-M3 muscarinic cholinergic autoantibodies from patients with primary Sjögren's syndrome trigger production of matrix metalloproteinase-3 (MMP-3) and prostaglandin E2 (PGE2) from the submandibular glands - Reina, Silvia Lorena (2011)
Background: We demonstrated that serum immunoglobulin G (IgG) from patients with primary Sjögren's syndrome (pSS), interacting with the second extracellular loop of human glandular M3 muscarinic acetylcholine receptors (M3 mAChR), trigger the production of matrix metalloproteinase-3 (MMP-3) and prostaglandin E2 (PGE2). Methods: Enzyme-linked immunosorbent assays (ELISAs) were performed in the presence of M3 mAChR synthetic peptide as antigen to detect in serum the autoantibodies. Further, MMP-3 and PGE2 production were determined in the presence of anti-M3 mAChR autoantibodies. Results: An association was observed between serum and anti-M3 mAChR autoantibodies and serum levels of MMP-3 and PGE2 in pSS patients. Thus, we established that serum anti-M3 mAChR autoantibodies, MMP-3 and PGE2 may be considered to be early markers of pSS associated with inflammation. Affinity-purified anti-M3 mAChR peptide IgG from pSS patients, whilst stimulating salivary-gland M3 mAChR, causes an increase in the level of MMP-3 and PGE2 as a result of the activation of phospholipase A2 (PLA2) and cyclooxygenase-2 (COX-2) (but not COX-1). Conclusions: These results provide a novel insight into the role that cholinoceptor antibodies play in the development of glandular inflammation. This is the first report showing that an antibody interacting with glandular mAChR can induce the production of pro-inflammatory mediators (MMP-3/PGE2).